Pengaruh kinerja lingkungan dan pengungkapan carbon accounting terhadap profitabilitas di perusahaan pertambangan yang terdaftar di BEI tahun 2021-2024 - Adytiya Arum Ningtias; Santosa Tri Prabowo; MG Sukamdiani (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to examine the impact of environmental performance and carbon accounting disclosure on the profitability of companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The study uses a quantitative approach with panel data regression analysis. The population in this study includes all companies in the mining sector listed on the IDX during 2021-2024, with the sample selection carried out using purposive sampling based on certain criteria. The data analysis process is conducted to assess the impact of environmental performance and carbon accounting disclosure on company profitability. The results of this study show that environmental performance and carbon accounting disclosure do not have a significant effect on the profitability of mining sector companies listed on the IDX between 2021 and 2024. Keywords: Environmental Performance, Carbon Accounting Disclosure, Profitability, Net Profit Margin ( NPM ), Mining Companies